Using CFD model of furnace for improvement of the quality of alumina-containing sinter. Issue 1 (25th February 2014) - V. Aleksandrov, Alexander; V. Aleksandrov, Valera
Abstract : Purpose: – The purpose of the study is to improve the quality of alumina-containing sinter produced in a rotary kiln. Simulating sintering furnace assessment of technical solutions aimed at creating optimal phase composition of clinker. Design/methodology/approach: – The computer model of the sintering furnace is developed. Influence of characteristics of material streams on thermal processes in the furnace was considered. Balance of energy, including heat conductivity, convection and radiant heat exchange has been solved in a stable state. Between actual and calculated variables of work of the furnace, good correlation was observed. Findings: – The evaluation of the effect of increasing primary air and fuel burner extension to changes in temperature of the material. The modeling found that the most effective solution to reduce the temperature of the sinter is lengthening fuel burner to 5 m. Practical implications: – The model can be applied to analyze and optimize the alteration of temperatures of materials and gases in an industrial furnace under various conditions. Originality/value: – The article provides new information for specialists in the production of alumina. For the first time shows the influence of cooling conditions on the alumina-containing sinter quality. According to the results of computer modeling, it has been established that for creating of optimal cooling conditions of the sinter in the furnace, the length of coal burner must be not less than 5 m.